The excellence management in developing marketing mix strategies for entrepreneurial institutions - Al-zoubi, Ali Falah; Alshare, Fathi Abdullah; Assamera, Zahed (Opción, 2019)
The aim of the research is to identify the relationship between the four marketing mix strategies of the leading companies in Jordan and their impact on their marketing performance via a descriptive research method. The study found that there is a significant relationship between the marketing strategies of the elements of the marketing mix in the leading Jordanian institutions and their marketing performance in its dimensions. In conclusion, there seems to be a difference in considering the relative importance of each element of the marketing mix of the managers of Jordanian institutions leading SMEs.